In search of management development in Europe : from self- fulfilling prophecies to organizational competence - Larsen, Henrik Holt [Verfasser] (My University, 1996)
This paper gives an overview and a critical analysis of the concept of High Flyer programmes in management development. Based on a discussion of the need for management development in modern knowledge- and service-based organizations, strengths and weaknesses of traditional management development programmes are discussed. In particular, the so-called 'fast-track' programmes for high-potential employees are presented. This analysis shows that, although management development is supposed to be a vital contributor to organizational competence, learning, and change. High Flyer Programmes are (still) mainly an instrument for individual and personal career development. An alternative interpretation of management development is presented which emphasizes the match between personal growth and organizational learning and which links career, organization development and competitive advantage of the organization. In conclusion, implications for practice and research are discussed. Quantitative results from the most recent Cranfield Network on European HRM Survey are presented and analysed. Der Artikel gibt einen Überblick und eine kritische Analyse von High-Flyer-Programmen, also von Personalentwicklungs- bzw. Personalförderungsprogrammen für besonders befähigte und förderungswürdige Mitarbeiter bzw. Führungs(nachwuchs)kräfte und deren schnellen Aufstieg. Präsentiert werden auch quantitative Ergebnisse der international-vergleichenden Cranfield Network on European HRM Survey von 1995.
Keywords: S 5.3 Personalentwicklung; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; I 2.2 Europa; I 2.1 Deutschland; I 2.2.1 Westeuropa; I 2.3.4 Asien; I 2.2.2 Osteuropa; Personalmanagement; Führungskraft; Personalentwicklung; Berufsverlauf; Planung; Berufliche Weiterbildung; Berufsausbildung; Managementtraining; Internationaler Vergleich; Europa; Deutschland; Spanien; Irland; Finnland; Schweiz; Frankreich; Niederlande; Italien; Türkei; Großbritannien; Dänemark; Schweden; 1995-1995